1995
DOI: 10.1002/cne.903610206
|View full text |Cite
|
Sign up to set email alerts
|

Oculomotor control in calliphorid flies: Organization of descending neurons to neck motor neurons responding to visual stimuli

Abstract: In insects, head movements are mediated by neck muscles supplied by nerves originating in the brain and prothoracic ganglion. Extracellular recordings of the nerves demonstrate units that respond to visual stimulation of the compound eyes and to mechanosensory stimulation of the halteres. The number of neck muscles required for optokinetic eye movements in flies is not known, although in other taxa, eye movements can involve as few as three pairs of muscles. This study investigates which neck motor neurons are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 39 publications
3
47
0
Order By: Relevance
“…These frontal nerve neck neurons in turn innervate the large sclerite depressor muscle involved in head-roll movements Gilbert et al, 1995). Previous studies showed that motor neurons of the frontal nerve are motion sensitive Gronenberg et al, 1995;Huston and Krapp, 2003;Krapp and Huston, 2005). Although the number of neck muscle and motor neurons is manageable Strausfeld et al, 1987), the neural circuit as well as the computations underlying these optomotor responses is complex and far from being understood.…”
Section: Functional Implicationmentioning
confidence: 99%
See 2 more Smart Citations
“…These frontal nerve neck neurons in turn innervate the large sclerite depressor muscle involved in head-roll movements Gilbert et al, 1995). Previous studies showed that motor neurons of the frontal nerve are motion sensitive Gronenberg et al, 1995;Huston and Krapp, 2003;Krapp and Huston, 2005). Although the number of neck muscle and motor neurons is manageable Strausfeld et al, 1987), the neural circuit as well as the computations underlying these optomotor responses is complex and far from being understood.…”
Section: Functional Implicationmentioning
confidence: 99%
“…Like DNOVS2, DNOVS1 projects from the axon terminals of VS cells into the thoracic ganglion and from there onto motor neurons (Strausfeld and Bassemir, 1985;Gronenberg et al, 1995). Both cells receive visual motion input via the VS cells and from the photoreceptors of the ocelli via L-neurons (Strausfeld and Bassemir, 1985;.…”
Section: Physiological Differences Between Dnovs1 and Dnovs2mentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the only reported example of an identified descending neuron that is selective for visual and olfactory cues. However, cells that integrate visual and mechanosensory information in other insects are not uncommon (Baader et al, 1992;Gronenberg et al, 1995;Olberg, 1981;Rowell and Reichert, 1986). Examining the physiological properties of as yet unidentified DNs in Drosophila will help define physiological mechanisms of sensorimotor superposition.…”
Section: Neuromuscular Mechanisms For Visuo-olfactory Sensorimotor Inmentioning
confidence: 99%
“…In this article, we present electrophysiological data on a specific descending neuron, the DNOVS1 (also called DNDC 1-1 by Gronenberg et al, 1995). Given the described connectivity to VS cells, we studied how the signals of a subset of VS cells and ocellar input are integrated on the dendrite of DNOVS1.…”
Section: Introductionmentioning
confidence: 99%